A study on the behaviour of impinging jets on curved surfaces - Woon, Kiat Weng (2014)
Extensive studies have been done before to understand the behavior of jet flows. Such flows include free jets from various geometries of nozzles. Besides free jets, the impingement of jets upon various surfaces and geometries have also been studied to obtain insights on the development of various coherent structures. These surfaces include flat plats and curved surfaces, but the amount of literature and work on the latter still leaves much to be understood. In this project, the study focuses on jet impingement from a flow using laser induced fluorescence for the purpose of flow visualization, and subsequent particle image velocimetry to conduct a quantitative analysis on the flow behavior.